Analisis Penggunaan Etos Pathos Logos dalam Pidato Dedi Mulyadi di Upacara Hari Kebangkitan Nasional “Bangkit Bersama Wujudkan Indonesia Kuat” - Ardila, Della; Febria, Rhani (UIR Press, 2025)
This study aims to analyze the elements of Aristotelian rhetoric, namely ethos, pathos, and logos, in Dedi Mulyadi's speech entitled